The political economy of Zambia’s recovery: Structural change without transformation? - Resnick, Danielle; Thurlow, James (International Food Policy Research Institute, 2017)
Long considered the archetype of economic decline in Africa, Zambia more recently has been heralded as an example of Africa’s economic resurgence. Thanks to rapid growth during the 2000s, the country reclaimed its “middle-income” status that had been lost after independence in 1964. This coincided with macroeconomic stability and a burgeoning consumer class, symbolized by the rising number of shopping malls in the capital city Lusaka. Such a rosy picture, however, contrasts sharply with the message presented by multiple scholars, civil society organizations, and political figures during the 2000s. They noted the sharp rise in the cost of living and service delivery for those in low-income neighborhoods (Simatele and Simatele 2009) and observed popular resentment toward signs of growing income disparities (Larmer and Fraser 2007). In addition, the veteran politician Michael Sata, who led the opposition Patriotic Front (PF) until he was elected president in 2011, repeatedly argued that the country had experienced rising unemployment and inequality under the tenure of Movement for Multiparty Democracy (MMD). Over the course of three elections between 2006 and 2011, Sata targeted his campaigns in Zambia’s major cities, where rapid urbanization contributed to large numbers of voters. His massive and sustained electoral support among those living in shanty compounds and working in informal markets suggested that his message regarding uneven transformation strongly resonated with a large share of the populace.